Makanan Halal dan Pengaruhnya Terhadap Kepribadian Anak Dalam Perspektif al-Qur’an.: Indonesia - parlindungan simbolon; Zalisman; Evi Rahayu (Sekolah Tinggi Ilmu Tarbiyah Al- Kifayah Riau, 2022)
This study aims to describe what is meant by halal food and whether halal food can influence a child's soul to become a pious person. The problem that must be resolved in this research is what is meant by halal food and whether halal food can influence a child's soul to become a righteous person. This research is descriptive qualitative research involving the documentation method. The data and information found are critically analyzed to formulate conclusions as a result of the research. The results of this study found that what is meant by halal food is food that is not prohibited in the texts either in the Qur'an or the Hadith. Consuming halal food will be able to influence the soul of a child from an early age to become a righteous and righteous person. On the other hand, haram food will hurt the physical health and reason and personality of the child.